The age of battles the quest for decis ive warfare from Breitenfeld to Waterloo - Weigley, Russell Frank; American Council of Learned Societies (Bloomington : Indiana University Press, 2004)
This book studies the battles of Gustavus, Charles II, Louis XIV, Ma rlborough, Nelson, Napoleon and Wellington during the period between 16 31 and 1815.
"First paperback edition ... 2004"--T.p. verso.
Originally published: 1991.
Includes bibliographical references (p. [545]-558) and index.
Electronic text and image data.
Description based on print version.
Keywords: Military art and science -- Europe -- History; Battles -- Europe -- History; Military history, Modern; Europe -- History, Military -- 1648-1789.